PENGARUH PENERAPAN MODEL ORGANIZING, REFLECTING TERHADAP KEMAMPUAN MENULIS TEKS BERITA PADA SISWA - SISWI SLTP - DORTYA . (LP2MTBM MAKARIOZ, 2021)
Influence is the force that exists or arises from a person, (person, thing) that contributes to the organization, beliefs, oractions of a person.